(untitled) (diségno, 2021)
The tools and methods aimed at the documentation of the built heritage often follow different paths depending on the own languages of the different frameworks involved in the knowledge process. It is clear how this assumption comes out when working in fragile contexts, where the risk of losing heritage due to natural and/or anthropic events is especially high. Therefore, in order to promote a multidisciplinary research approach, is often necessary to find a connection, even on methods, able to allow to reach in a shared way the common goal of the knowledge aimed to the conservation and communication of the heritage. Herein are presented the results of a research study aimed at testing the potential of a digital system for the integration of the languages of two fields: architectural drawing and architectural archaeology. Our spotted tool, the Virtual Tour, is flexible and easy-to-use, and when properly designed, it became a hub capable of linking several thematic readings and make them available, in addition to the various professionals, also to a wider audience, promoting the managing of the Cultural Heritage by the institutions-owners and the heritage’s fruition. This tool’s potential is here outlined through the application to a case of study, the church of San Menna at Lucoli (AQ) characterized, despite its small size, by different constructive phases and by a rich decorative apparatus of great historic-artistic value.